Gaseous and particulate emissions from a chimneyless biomass cookstove equipped with a potassium catalyst. (1st February 2019) - Paulsen, Alex D.; Kunsa, Tyler A.; Carpenter, Andrew L.; Amundsen, Ted J.; Schwartz, Nicholas R.; Harrington, Jason; Reed, Jackson; Alcorn, Brett; Gattoni, John; Yelvington, Paul E.
Graphical abstract: Highlights: Potassium titanate was an effective catalyst for soot and carbon monoxide oxidation. Catalyst deactivation was caused by loss of potassium from the catalyst surface. Cookstove emissions were sensitive to small, draft-related design changes. Particulate matter emissions were reduced in standardized water boil tests. Abstract: Approximately three billion people cook with solid fuels, mostly wood, on open fires or rudimentary stoves. These traditional cooking methods produce particulate matter and carbon monoxide known to cause significant respiratory health problems, especially among women and children, who often have the highest exposure. In this work, an inexpensive potassium-based catalyst was incorporated in a chimneyless biomass cookstove to reduce harmful emissions through catalytic oxidation. Potassium titanate was identified as an effective and stable oxidation catalyst capable of oxidizing particulate matter and carbon monoxide. Using a cordierite monolith to incorporate potassium titanate within a bespoke, rocket-style, improved cookstove led to a 36% reduction in particulate matter emissions relative to a baseline stove with a blank monolith and a 26% reduction relative to a stove with no monolith. Additionally, the catalytic stove reduced particulate matter emissions by 82%, reduced carbon monoxide emissions by 70%, and improved efficiency by 100% compared to a carefully tended, three-stone fire. Potassium titanate was also shown to oxidize carbon monoxide at temperatures as low as 500 °C, or as low as 300 °C when doped with copper or cobalt.